The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/498987
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for HIV/Syphilis Infection and Male Circumcision Practices and Preferences among Men Who Have Sex with Men in China

Abstract: Objective. To investigate factors associated with HIV infection and the frequency and willingness of male circumcision among men who have sex with men (MSM) in Chengdu city, China. Methods. A cross-sectional survey provided information on participants' demographics, risk behaviors, circumcision, and uptake of HIV prevention services. Results. Of 570 participants, 13.3% were infected with HIV and 15.9% with syphilis. An estimated 43.0% of respondents reported having unprotected receptive anal intercourse, and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
3
20
0
2
Order By: Relevance
“…In addition, this study corroborates the findings of earlier studies in regard to the independent correlation of HIV infection among total MSM and all three MSM subgroups with various other factors including recreational drug use, syphilis infection and HSV-2 infection 5 10. The public health services need, therefore, to enhance their understanding of recreational drug use among MSM, and further develop interventions to target high-risk sexual behaviours and encourage engagement with care among that population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, this study corroborates the findings of earlier studies in regard to the independent correlation of HIV infection among total MSM and all three MSM subgroups with various other factors including recreational drug use, syphilis infection and HSV-2 infection 5 10. The public health services need, therefore, to enhance their understanding of recreational drug use among MSM, and further develop interventions to target high-risk sexual behaviours and encourage engagement with care among that population.…”
Section: Discussionsupporting
confidence: 87%
“…Investigations into the influence of migration status on the odds of HIV infection have produced equivocal results 5 6. Recent studies have suggested that migrants exhibit noticeable variation in high-risk sexual behaviours depending on their duration of residence.…”
Section: Introductionmentioning
confidence: 99%
“…In our Beijing urban study, we observed an HIV prevalence of 12.7%, substantially higher than the latest national estimate (7.3%), 48 and similar to the findings documented in recent studies among Chinese MSM in other metropolitan areas (12.4%–14.5%). 43,49–51 MSM had a high HIV prevalence in Beijing, confirming our mathematical projection that the HIV epidemic continues to grow in this key population. 24 Consistent with other findings, 42,5154 we found familiar risk factors among HIV-positive MSM, including younger age of sexual debut, lower educational level, never married, transient residence, more lifetime male sexual partners, ever engaging in condomless anal sex, drug use, and alcohol use before sex.…”
Section: Discussionsupporting
confidence: 74%
“…Circumcision rates among MSM remain low (<20%) in countries such as Thailand 76 or China. 182,183 Although a recent study in India suggests that circumcised MSM who predominantly take the receptive role in anal intercourse may be at a lower risk of HIV infection, 184 evidence that circumcision reduces HIV among MSM remains weak and inconsistent. 185,186 Despite the willingness to undergo circumcision among MSM populations, 187,188 male circumcision is not promoted as a priority in Asian countries with concentrated epidemics and has not been recommended for MSM unless they also engage in vaginal sex.…”
Section: Implications For Hiv Prevention Trialsmentioning
confidence: 99%